Applying Mesoporous Silica SBA‐15 in Electrochemical Detection of DNA Hybridization. Issue 8 (13th April 2016) - Josypčuk, Oksana; Fojta, Miroslav; Daňhel, Aleš; Josypčuk, Bohdan
Abstract: Mesoporous silica SBA‐15 powder was used as the separation surface for hybridization purposes and it has proved appropriate and effective. By help of a simple procedure any oligodeoxynucleotide (ODN) modified by NH2 ‐group can be covalently bound at the surface of SiO2 particles, what significantly extends the capabilities of the experimenter. Use of cathodic stripping voltammetry for electrochemical detection of ODN/DNA hybridization ensures high sensitivity of the analyses. Only ordinary laboratory equipment is needed for the implementation of these experiments. Due to the very small consumption of SBA‐15, commonly sold quantity (5 g) may be sufficient for many years of work. Abstract :